Analisis Hubungan Health Literacy dengan Tingkat Kepatuhan Minum Obat pada Pasien Diabetes Melitus Tipe II di RSUD Arifin Achmad Pekanbaru - Denia Pratiwi; Rahmadinni Rahmadinni; Nadya Putri Auliya Serawaidi (JURNAL PROTEKSI KESEHATAN, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic disease requires long-term treatment. Low medication adherence influenced by poor health literacy, poses a significant challenge in managing T2DM. This study aimed to asses the relationship between both variables among T2DM outpatients at Arifin Achmad Hospital, Pekanbaru. This research used a quantitative analytic design with a cross-sectional approach with a total of 88 respondents. Data were collected using the HLS-EU-Q16 questionnaire for health literacy and the MMAS-8 for medication adherence, then analyzed using the Chi-Square test. Results showed that health literacy category 35.2% (low); 31.8% (moderate); 33% (high). For medication adherence category were 37.5% (high) ; 30.7% (moderate); 31.8% (low). Statistical analysis revealed a significant relationship between health literacy and medication adherence (p = 0.003, p < 0.05). Occupational status have factor significantly related to adherence (p = 0.012). Enhancing health literacy is important to support long-term medication adherence among T2DM patients